A case for cautious optimism? Active citizenship and the Australian civics and citizenship curriculum. Issue 1 (2nd January 2017) - Peterson, Andrew; Bentley, Brendan
Abstract: In late 2013 a new curriculum for Civics and Citizenship education was published by the Australian Curriculum and Assessment Reporting Authority for use in Australian schools. In line with previous curricular initiatives concerning education for citizenship in Australia a key rationale behind the new subject is the education of "active citizens". Research evidence over the last 25 years paints a mixed picture regarding the extent to which the translation of policy intent has been successfully implemented within Australian schools. Exploring the new subject of Civics and Citizenship in Australia in the context of previous initiatives and existing research evidence, we explore the contested and complex nature of active citizenship around three key issues – the scope and form of action that constitutes citizenship in one's communities, how young people themselves conceptualize and experience participation, the potential that active citizenship opportunities are interpreted as being synonymous with the use of active teaching and learning methods. On this basis we argue that the new curriculum provides some optimism for those committed to education for citizenship in Australian schools, but that this optimism needs to be tempered with a degree of caution.